Informal caregivers of patients with disorders of consciousness: Experience of ambiguous loss. (April 2015) - Giovannetti, A. M.; Černiauskaitė, M.; Leonardi, M.; Sattin, D.; Covelli, V.
Abstract Primary objective: This study aimed at better understanding of the complex psychological process underlying the demanding situation of taking care of a relative with disorder of consciousness (DOCs). Research design: This is a qualitative study based on the grounded theory constant comparative method. Methods and procedures: Narratives of informal caregivers were collected through in-depth interviews with a psychologist. A three-step coding scheme was applied: coding of narratives to label the specific contents; organization of codes into sub-categories and categories; and theoretical coding to describe the relation between categories. Main outcomes and results: Twenty informal caregivers participated in one in-depth interview between December 2011 and May 2012. Four major themes emerged: Another person with past in common; Losing and finding myself; Old and new ways of being in relationship; and Dealing with concerns. These themes represent caregivers' efforts to deal with the situation in which their relative is at the same time present and absent. The core salient feature emerging from all these themes is the experience of ambiguous loss. Conclusions: Features of ambiguous loss that emerged in this study could guide clinicians' interventions to support adjustment of caregivers of patients with DOCs.